Hubungan Asupan Lemak dengan Indeks Massa Tubuh (IMT) dan A Body Shape Index (ABSI) pada Remaja SMA di Surakarta - Ashillah Putri Sakhroni; Dyah Intan Puspitasari; Firmansyah - (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Adolescence is a critical period of growth and development characterized by rapid physical changes and alterations in body composition, increasing the need for adequate nutritional intake, including fat. Excessive or insufficient fat intake can affect body composition and abdominal fat distribution. This study aimed to analyze the association between fat intake and nutritional status based on Body Mass Index-for-Age (IMT/U) as well as abdominal fat distribution based on A Body Shape Index (ABSI) among high school adolescents in Surakarta. This observational analytic study employed a cross-sectional design and was conducted in February 2025 at four public senior high schools in Surakarta. A total of 200 respondents aged 15–18 years were selected using multistage random sampling. Data collection included anthropometric measurements consisting of body weight, height, and waist circumference, as well as dietary assessment using three non-consecutive 24-hour food recalls comprising two weekdays and one weekend day. Nutrient intake data were analyzed using NutriSurvey software. Nutritional status was assessed using WHO IMT/U z-score standards, while abdominal fat distribution was assessed using ABSI. Data were analyzed using Pearson Product Moment correlation test for IMT/U and Spearman Rank correlation test for ABSI. The results showed no significant association between fat intake and IMT/U (p=0.868, r=0.012) or ABSI (p=0.988, r=0.001). In conclusion, fat intake alone was not significantly associated with IMT/U or abdominal fat distribution among adolescents. These findings indicate that nutritional status and abdominal fat distribution in adolescents are multifactorial conditions that cannot be explained solely by fat intake.